New protocol for kinetic assay seeding ability recovery “KASAR” from formalin-fixed paraffin-embedded tissues - Monica Hepker; Griffin Clabaugh; Huajun Jin; Anumantha G. Kanthasamy; Anumantha G. Kanthasamy (Frontiers in Molecular Biosciences, 2023)
The real-time quaking-induced conversion (RT-QuIC) alpha-synuclein (aSyn) protein kinetic seeding assay has been very useful for detecting pathological aggregates in various synucleinopathies including Parkinson’s disease (PD). This biomarker assay relies on fresh frozen tissue to effectively seed and amplify aSyn aggregating protein. With vast repositories of formalin-fixed paraffin-embedded (FFPE) tissues, it is paramount to harness the power of kinetic assays to unlock the diagnostic potential of archived FFPE biospecimens. However, the major challenge posed by significantly reduced amplification of formalin-fixed tissues in the assay suggests that formalin fixation deterred monomer interaction with the sample seed and depressed subsequent protein aggregation. To overcome this challenge, we developed a kinetic assay seeding ability recovery (KASAR) protocol to maintain the integrity of the tissue and seeding protein. For this, we implemented a series of heating steps with the brain tissue suspended in a buffer composed of 500 mM tris-HCl (pH 7.5) and 0.02% SDS after the standard deparaffinization of the tissue sections. Initially, samples from seven human brain samples, including four samples from patients diagnosed with dementia with Lewy bodies (DLB) and three samples from healthy controls without DLB, were compared to fresh frozen samples under three different, but clinically common sample storage conditions: formalin-fixed, FFPE, and FFPE slices cut 5 µm thick. The KASAR protocol was able to recover seeding activity for all positive samples in all storage conditions. Next, 28 FFPE samples from the submandibular gland (SMG) of patients diagnosed with PD, incidental Lewy body disease (ILBD), or healthy controls were tested with 93% of results replicating when blinded. With samples of only a few milligrams, this protocol recovered the same quality of seeding in formalin-fixed tissue as fresh frozen tissue. Moving forward, protein aggregate kinetic assays, in conjunction with the KASAR protocol, can be used to understand and diagnose neurodegenerative diseases more comprehensively. Overall, our KASAR protocol unlocks and restores the seeding ability of formalin-fixed paraffin-embedded tissues for the amplification of biomarker protein aggregates in kinetic assays.